Planning focus groups - Morgan, David L. (Sociologist); Scannell, Alice U.; Sage eBooks (London : SAGE, 1998)
'Planning Focus Groups' is part of the six-volume Focus Group Kit which offers the information needed to conduct a state-of-the-art focus group, from the initial planning stages through to analysing and reporting the data.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Focus groups; Electronic books